Program Pertukaran Dosen Antar LPTK: Sebuah Upaya Peningkatan Kualitas Pembelajaran - Muhyadi Muhyadi (Efisiensi : Kajian Ilmu Administrasi, 2010)
The study was aimed to find out the perception of students, lectures, and management on: 1) the implementation of lecturer exchange program between four universities, 2) the constraints against in the program implementation, and 3) the perspective of the collaborative program in the future. The study was conducted in the Faculty of Social Sciences and EconomiC, Yogyakarta State University in the 2005/2006 academic year.· The study was an evaluation research intended to evaluate the implementation of collaborative program especially lecturer exchange between four universities (FISE UNY, FIS UNNES, FIS UNESA, and FKIP UNS). Data were collected using questionaire given to the students, lectures, and management of the collaborative program in the Faculty of Social Sciences and Economic, YSU (the dean and his staffs and the head of study program). The results of the study. were: most of students perception on the program were positive, they took something useful and valuable from the implementation of the program, and their knowledge and competencies were increased. Lecturers involves in the program feel that the program was effectively conducted since it increased the quality of teaching-learning process and their professionalism. That is why they proposed to continue the implementation of the program in the future. The other interesting result was the intention to implement the program collaborative to the broader area such as textbook writing, teaching model development, and collaborative research. The constraints against the implementationof the program were lack of funds and problems in matching schedule between lecturers from other universities.